Relasi antara Pergeseran Peran Pencari Nafkah dan Krisis Maskulinitas dalam Cerpen “Huruf Terakhir” karya Benny Arnas - Marta Widyawati (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
This research aims to show the masculinity crisis experienced by a male character (a husband) due to the shift role of breadwinner in marriage in the short story